Efficacy of anti‐programmed cell death‐1 immunotherapy for skin carcinomas and melanoma metastases in a patient with xeroderma pigmentosum. (1st May 2018) - Salomon, G.; Maza, A.; Boulinguez, S.; Paul, C.; Lamant, L.; Tournier, E.; Mazereeuw‐Hautier, J.; Meyer, N.
Summary: Xeroderma pigmentosum (XP) is an orphan disease of poor prognosis. We report one case of parallel efficacy with anti‐programmed cell death‐1 (PD‐1) antibody on both melanoma and skin carcinoma in a patient with XP. A 17‐year‐old patient presented with metastatic melanoma and multiple nonmelanoma skin cancers. He was treated with pembrolizumab, a monoclonal anti‐PD‐1 antibody, at a dose of 2 mg kg −1, every 3 weeks. Parallel therapeutic efficacy of anti‐PD‐1 was observed in metastatic melanoma and skin carcinomas, and maintained at week 24. This observation suggests anti‐PD‐1 may be considered in patients with XP and metastatic melanoma in addition to advanced nonmelanoma skin cancer.